Pelaksanaan Informed Consent pada Pemeriksaan Intra Vena Pyelografi di Instalasi Radiologi Rumah Sakit Umum Sukoharjo - Rini Indrati; Meita Shinta Fatikhatul Laila; Andrey Nino Kurniawan (Poltekkes Kemenkes Semarang, 2017)
Background: The implementation of informed consent at Radiology department of Sukoharjo Hospital was conducted by administrative officer and radiographer. The officer explained the preparation of pyelographic intra-venous examination to the patient then the patient was asked to fill out and sign the informed consent form. According to the Indonesian Medical Council and Regulation of the Minister of Health of Indonesia, the delivery of informed consent is carried out by doctors. The doctor explains all the information contained in the contents of informed consent before taking any medical action. The purpose of this research is to know the implementation of informed consent done in the radiology department and patient understanding of the contents of the informed consent form.Methods: The type of this research is descriptive qualitative research with the observational approach. Data were collected in March-June 2017 by observational of informed consent and interviews of 30 patients who will conduct intra vena pyelographic examination. Data analyzed by descriptively.Results: The results showed that the provision of informed consent to intravenous pyelographic examination patient at Sukoharjo Hospital was performed by administration officer and radiographer before conducting the examination. The patient's understanding of the contents of informed consent has not been in accordance with the content of the informed consent form because the information submitted by the radiologist only concerning the preparation of intravenous examination of pyelography does not include examination procedures, objectives, risks, complications, diagnoses, prognoses, alternative other measures and risks, and costs.Conclusions: In radiology department of Sukoharjo hospital at Intravenapyelography patient informed consent delivered by administrative officers and radiographer. Patients understanding the content of informed consent